Unraveling the Microbial Interactions and Metabolic Potentials in Pre- and Post-treated Sludge from a Wastewater Treatment Plant Using Metagenomic Studies - Sidhu, Chandni; Vikram, Surendra; Pinnaka, Anil Kumar (Frontiers in Microbiology, 2017)
Sewage waste represents an ecosystem of complex and interactive microbial consortia which proliferate with different kinetics according to their individual genetic as well as metabolic potential. We performed metagenomic shotgun sequencing on Ion-Torrent platform, to explore the microbial community structure, their biological interactions and associated functional capacity of pre-treated/raw sludge (RS) and post-treated/dried sludge (DS) of wastewater treatment plant. Bacterial phylotypes belonging to Epsilonproteobacteria ( 45.80%) dominated the RS with relatively few Archaea ( 1.9) whereas DS has the dominance of beta- (30.23%) and delta- (13.38%) classes of Proteobacteria with relatively greater abundance of Archaea ( 7.18%). In particular, Epsilonproteobacteria appears as a primary energy source in RS and sulfur-reducing bacteria with methanogens seems to be in the potential syntrophic association in DS. These interactions could be ultimately responsible for carrying out amino acid degradation, aromatic compound degradation and degradation of propionate and butyrate in DS. Our data also reveal the presence of key genes in the sludge microbial community responsible for degradation of polycyclic aromatic hydrocarbons. Potential pathogenic microbes and genes for the virulence factors were found to be relatively abundant in RS which clearly reflect the necessity of treatment of RS. After treatment, potential pathogens load was reduced, indicating the sludge hygienisation in DS. Additionally, the interactions found in this study would reveal the biological and environmental cooperation among microbial communities for domestic wastewater treatment.